Fostering organisational commitment: a resilience framework for private-sector organisations in South Africa - Mujajati, Ester; Ferreira, Nadia; du Plessis, Melissa (Frontiers in Psychology, 2024)
Introduction Organisations worldwide encounter three significant and challenging issues related to talent management: intense competition for skilled employees, elevated rates of employee attrition, and the ongoing struggle to attract top-tier talent. This research focused on investigating the interconnected dynamics among factors associated with employee retention, including organisational commitment, job embeddedness, and hardiness, in conjunction with resilience-related behaviours such as resilience and career adaptability. Methods A cross-sectional survey design was used to gather quantitative data from a convenience sample of employees within the private sector in South Africa (N = 293). The self-assessments of the participants were assessed using a range of well-established and validated instruments. Correlation and regression analyses, followed by structural equation modelling, were utilised to construct a resilience framework designed specifically for private sector organisations in South Africa. Results The results reveal significant associations between organisational commitment, job embeddedness, and hardiness (as retention-related attributes) and resilience and career adaptability (as resilience-related behavioural capacities). These relationships served as the basis for the development of a resilience framework for employees in South African private organisations. Discussion In South African private-sector organisations, talent retention is crucial due to a talent shortage. The study found that employees have a strong emotional attachment to their organisations, are highly aligned with their jobs and communities, and display resilience. Organisational commitment, job embeddedness, and hardiness are key factors in reducing turnover, forming an effective retention strategy. This research contributes to the development of a resilience framework for South African private sector organisations.